Method development for frame design of electric motorcycles - Blixt, William; Lokat, Adil (My University, 2023)
Compliance in a motorcycle frame is an important factor to consider when designing. Different load cases must be taken into consideration depending on the requirements of the bike and what the use case is. To think of the structural characteristics when designing can make the design process simpler and quicker. Extensive studies can take time and are not always necessary in early design if simple simulations has been done through the process. Early simulations can direct the design along the way to give good structural efficiency and smart solutions when integrating components as stressed members. To also have the simulations verified and calibrated to a physical test give confidence when doing simple iterative tests early in the design phase. A method has been developed to enable iterative and fast design development of a motorcycle frame with consideration to structural characteristics, and to do this with limited access to tools. To allow for this the design must continuously consider the structural simulations to not end up with a overly complex model that requires big changes after simulating. Results show that the method used to design and simulate, can have an impact on what and how the results obtained from simulation can differ from each other and thus be less suitable for different scenarios.